2014
DOI: 10.5123/s1679-49742014000200017
|View full text |Cite
|
Sign up to set email alerts
|

Perfil entomológico e epidemiológico da malária em região garimpeira no norte do Mato Grosso, 2011

Abstract: Objetivo: descrever o perfil entomológico e epidemiológico da malária em área de garimpo do município de Nova Guarita, estado de Mato Grosso, Brasil. Métodos: estudo descritivo com dados entomológicos e epidemiológicos da localidade Garimpo Grota da Lagoa, registrados no sistema de informação de vigilância epidemiológica da malária (SIVEP-malária) em 2011. Resultados: foram identificados 481 exemplares de vetores do gênero Anopheles; houve predominância de Anopheles darlingi nos ambientes pesquisados (42,6%); … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 12 publications
(21 reference statements)
0
2
0
5
Order By: Relevance
“…A região Norte do Brasil é considerada zona endêmica de doenças infectocontagiosas, como hanseníase, síndrome da imunodeficiência humana adquirida (AIDS), leishmaniose, malária, leptospirose, tuberculose e hepatite 7,8,9,10,11,12,13,14 . E, ainda, configura local de doenças reemergentes como cólera e febre tifoide 12,15 .…”
Section: Introductionunclassified
“…A região Norte do Brasil é considerada zona endêmica de doenças infectocontagiosas, como hanseníase, síndrome da imunodeficiência humana adquirida (AIDS), leishmaniose, malária, leptospirose, tuberculose e hepatite 7,8,9,10,11,12,13,14 . E, ainda, configura local de doenças reemergentes como cólera e febre tifoide 12,15 .…”
Section: Introductionunclassified
“…RibeiRo et al (2013) found a high prevalence in the period from 18:00 at 19:00 h of An. darlingi, using human bait technique in the period -2006. maciel & oliveiRa (2014 collected 481 specimens of the genus with peak of greater activity from 18:00 at 21:00 h.…”
Section: Resultsmentioning
confidence: 99%
“…In Brazil, the Amazon region accounts for 99% of malaria cases, and the incidence of malaria in gold mining regions is proportional to deforestation, being present in 39 cities of this biome [72,73]. Although the incidence rates may be even higher (31.3 to 94%), there has been a reduction in recent years in response to control programs implemented by public health services, which can be seen in the gold mining region in Colniza, where there was a seroprevalence of 4.5% [14,15,16,44,74,75].…”
Section: Discussionmentioning
confidence: 99%